Selection to Stem Rot Disease Athelia rolfsii (Curzi)Resistant Level of SomeSoybean (Glycine max L. Merrill)Line and High Production on M5 Generation - Mutia Rahmah; Diana Sofia Hanafiah; Luthfi Aziz Mahmud Siregar (Jurnal Agroekoteknologi, 2018)
This study aims to get individuals selected of some soybean Glycine max L. (Merrill) M5 generation with character resistant stem rot disease Athelia rolfsii (Curzi)and high production. This research was conducted in Plant Disease Laboratory and experimental field Faculty of Agriculture Universitas Sumatera Utara Medan, Indonesia. This research was conducted from December 2016 until July 2017. In this study using augmented design. The treatments were 15 mutant lines, the check variety were Anjasmoro, Agromulyo, and Kipas Putih varieties. The results showed that the appearance of agronomic characters observed in the inoculated medium of the fungus causes stem rot disease is lower than the optimum field without inoculation of fungus. Differences in the means values of the mutant line are in the larger stem diameter character of plant than with the inoculation of fungus.  Broad sense heritability values were found in the number of pods per plant, number of seeds per plant, and seed weight per plant on the inoculated medium of the fungus and the optimum field. Selection performed on population M5resulted 7 individuals with high production character and 62 individuals with tolerance of stem rot disease character.